Speech Order - Delgado, Honorio (1952)
Among the pleasant memories of my initiation into learning medicine excels, back in 1912, the study of histology. Made with objective criteria, all students did tissue preparations that were reviewed and scored by the professor of the course Dr. Daniel Eduardo Lavorería whose theoretical lessons exelentes captivated our interest for their precision and elegance.